Microbiome-macrophage crosstalk in the tumor microenvironment: implications for oral squamous cell carcinoma progression and therapy - Deng, Xin; Huang, Shaohong (Frontiers in Immunology, 2025)
Oral squamous cell carcinoma (OSCC) remains a formidable malignancy with persistently poor clinical outcomes. Recent research has underscored the pivotal role of the innate immune system, particularly tumor-associated macrophages (TAMs), a key component of the myeloid lineage, in orchestrating the tumor microenvironment (TME) and shaping disease progression. As professional phagocytes of the innate immune system, macrophages not only mediate pathogen recognition and inflammatory responses but also undergo functional polarization in response to local cues. In OSCC, dysbiosis of the oral microbiota, marked by the overrepresentation of species such as Fusobacterium nucleatum and Porphyromonas gingivalis—acts as a chronic inflammatory trigger that promotes epithelial-mesenchymal transition (EMT), immune evasion, and tumor growth. These pathogenic bacteria actively engage innate immune signaling pathways such as TLRs and CSF-1R, skewing macrophages toward an immunosuppressive M2 phenotype. M2-like TAMs then contribute to tumor progression by secreting anti-inflammatory cytokines (IL-10, TGF-β), promoting angiogenesis, and expressing immune checkpoint ligands such as PD-L1. This review summarizes current knowledge on the bidirectional crosstalk between dysbiotic microbiota and innate immune macrophages in OSCC, highlighting key receptor-mediated pathways and their implications for immune suppression, metastasis, and therapy resistance. Targeting microbiota modulation or innate immune reprogramming represents a promising strategy for restoring anti-tumor immunity and enhancing therapeutic efficacy in OSCC.